Benchmark data set for wheat growth models: Field experiments and AgMIP multi-model simulations - Asseng, Senthold; Ewert, Frank; Martre, Pierre; Rosenzweig, Cynthia; Jones, Jim; Hatfield, Jerry L.; Ruane, Alex C.; Boote, Kenneth J.; Thorburn, Peter J.; Rötter, Reimund P.; Cammarano, Davide; Basso, Bruno; et al. (Wageningen University & Research, 2015)
The data set includes a current representative management treatment from detailed, quality-tested sentinel field experiments with wheat from four contrasting environments including Australia, The Netherlands, India and Argentina. Measurements include local daily climate data (solar radiation, maximum and minimum temperature, precipitation, surface wind, dew point temperature, relative humidity, and vapor pressure), soil characteristics, frequent growth, nitrogen in crop and soil, crop and soil water and yield components. Simulations include results from 27 wheat models and a sensitivity analysis with 26 models and 30 years (1981-2010) for each location, for elevated atmospheric CO2 and temperature changes, a heat stress sensitivity analysis at anthesis, and a sensitivity analysis with soil and crop management variations and a Global Climate Model end-century scenario.